RELATIONSHIP BETWEEN FAMILY INCOME, HEALTH CHECK-UP AND NUTRITIONAL STATUS OF BADJAO PREGNANT MOTHERS IN SOUTHEAST SULAWESI, INDONESIA - Hariani Hariani; Tress Paukiran; Saktian Taskawati (Public Health of Indonesia)
Background: The nutritional status of pregnant women is strongly influenced by food intake and the presence of infectious diseases. Other factors that also affect the nutritional status of pregnant women are family income and health services.